Two distinct Ras genes from Puccinia striiformis exhibit differential roles in rust pathogenicity and cell death. (12th July 2016) - Cheng, Yulin; Wang, Wumei; Yao, Juanni; Huang, Lili; Voegele, Ralf T.; Wang, Xiaojie; Kang, Zhensheng
Summary: Ras genes have been shown to regulate a variety of cellular processes in higher eukaryotes. However, much less is known about their function(s) in fungi, especially plant pathogenic fungi. Here, we report the identification and functional analysis of Ras genes from Puccinia striiformis f. sp. tritici ( Pst ), an important fungal pathogen in wheat production worldwide. Pst contains two Ras genes, PsRas1 and PsRas2, which share 48.6% similarity at the protein level and fall into two different phylogenetic clades. Both PsRas1 and PsRas2 have conserved protein sequences among different Pst isolates, but exhibit different transcript profiles during Pst infection. Silencing of PsRas1 or PsRas2 indicates that PsRas2 but not PsRas1 contributes significantly to rust pathogenicity. However, overexpression of PsRas1, but not PsRas2, promotes cell death in yeast and plants. Further studies show that all conserved domains of Ras GTPases in PsRas1 are needed to induce this cell death. In plants, PsRas1 ‐triggered cell death shows similar characteristics as plant hypersensitive response. Our findings suggest that PsRas1 and PsRas2 take over different functions in rust pathogenicity and cell death, thus facilitating the understanding of cell death, pathogenic mechanisms of plant pathogenic fungi and the search for novel pathogen control strategies.